PENGARUH BIAYA DISTRIBUSI DAN PROMOSI TERHADAP VOLUME PENJUALAN PRODUK PADA PT ENSEVAL PUTERA MEGATRADING Tbk. (KALBE GROUP) - Hugo Aries Suprapto; Muhammad Rusdi (Universitas Indraprasta PGRI, 2015)
This study aims to determine influence the leadership style and quality of : (1) distribution costs and the costs of promotion to sales volume, (2) the costs of promotion to sales volume, and (3) the costs of distribution to sales volume. This study population is an employee of PT. Enseval Putera Megatrading Tbk, amounting to 257 people. Study sample as many as 60 people taken at random. Leadership style to give a significnt effect on the performance of employer. This results of data processing, te value tcount = 5,024 > ttable on ? value 5% = 1,671. Quality distribution costs to give a significant effect on sales volume. Data processing results obtained tcount value = 2,140 > ttable on ? value 5% = 1,671 . The results of this study indicate that distribution costs and the costs of promotion together to give a sales volume. Performance data processing results the coefficient of determination (R2) of o.73% means 73% improvement in sales volume is influenced by distribution costs and the costs of promotion, while the remaining 27% (100% - 73%) affected by other factors not analyzed. Key Words : distribution costs, promotion costs, and sales volume